THE TECHNO-ECONOMIC EVALUATION OF THE BETWEEN A GRID EXTENSION AND HYBRID RENEWABLE SYSTEMS CONSIDERING DEFERRABLE LOADS - Demirci, Alpaslan (International Journal of Research -GRANTHAALAYAH, 2023)
The rapid depletion of fossil energy resources significantly increases the need for renewable energy resources (RES) in electricity production. Hybrid power systems (HPS) are a promising solution for rural electrification where grid extensions are uneconomical. This study investigated the technical, economic, and environmental aspects of on-grid or off-grid HPS performance for optimal rural electrification. In addition, the effects of different deferrable load values on grid extension distance (GE) and optimal off-grid system sizing were investigated. Sensitivity analyses were conducted to evaluate the effects of variations in solar irradiation potential, diesel fuel costs, and discount rates on optimal HPS sizing. In scenarios where the deferrable load is above 9%, the GEs were zero, while below 5%, they increased to 24.2 km. In contrast, when the diesel generator (DG) was integrated into HPS, the photovoltaic (PV) and energy storage system (ESS) capacities were reduced by half in the optimal scenarios, and it was found that the GE was zeros regardless of the deferrable load. In the case of the highest deferrable load, the NPC is 22.6% lower than when there is no deferrable load. NPC surpasses the energy cost in the grid-only condition when solar irradiation is less than 4 kWh/m2/day, and ESS cost multipliers are greater than 2. This study will help researchers find optimal electrification solutions that support hybrid renewable energy and environmentally friendly options.